Evolving patterns of insurgency in Southern and West Africa: Refocusing the Boko Haram lens on Mozambique. Issue 4 (2nd October 2021) - Okunade, Samuel Kehinde; Faluyi, Olumuyiwa Temitope; Matambo, Emmanuel
ABSTRACT: Insurgency has gained prominence in Africa. It is usually associated with marginalisation, poverty, and inequality and often has religious links and bases. Insurgency frequently originates in communities situated along the borders of a country but soon spreads to neighbouring countries due to the poor response from the concerned state. The literature reveals that when state institutions ignore insurgent groups, they utilise that window of time to network with terrorist organizations such as Al-Qaeda and the Islamic State (IS) to solicit funds, arms and ammunition and training of new recruits and existing members. This was the case with Boko Haram, which was initially ignored by the Nigerian government only for it to become a security threat to the entire West African sub-region. An Islamic group, Ahlu Sunnah Wal Jammah (ASWJ) has recently emerged in Mozambique's Cabo Delgado Province with the aim of creating an Islamic state within the region. Drawing from the Boko Haram experience in West Africa, this article critically assesses the short- and long-term security threats that this group poses to Mozambique and the Southern African Development Community (SADC) and explores the strategies that could be deployed to combat the insurgency before it becomes a fully-fledged security challenge.